2021
DOI: 10.3390/jof7080644
|View full text |Cite
|
Sign up to set email alerts
|

Batrachochytrium salamandrivorans Threat to the Iberian Urodele Hotspot

Abstract: The recent introduction of the chytrid fungus Batrachochytrium salamandrivorans into northeastern Spain threatens salamander diversity on the Iberian Peninsula. We assessed the current epidemiological situation with extensive field sampling of urodele populations. We then sought to delineate priority regions and identify conservation units for the Iberian Peninsula by estimating the susceptibility of Iberian urodeles using laboratory experiments, evidence from mortality events in nature and captivity and infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…The fungi Batrachochytrium dendrobatidis (Longcore, Pessier, and D.K. Nichols (1999)) and Batrachochytrium salamandrivorans (Martel A., Blooi M., Bossuyt F., Pasmans F. ( 2013)) (Batrachochytriaceae), which produce chytridiomycosis, have been detected in Spain [55], and experimental studies have shown that these amphibians are at risk [56]. Since 2018, an outbreak of the deadly fungus B. salamandrivorans has been detected in Barcelona.…”
Section: Discussionmentioning
confidence: 99%
“…The fungi Batrachochytrium dendrobatidis (Longcore, Pessier, and D.K. Nichols (1999)) and Batrachochytrium salamandrivorans (Martel A., Blooi M., Bossuyt F., Pasmans F. ( 2013)) (Batrachochytriaceae), which produce chytridiomycosis, have been detected in Spain [55], and experimental studies have shown that these amphibians are at risk [56]. Since 2018, an outbreak of the deadly fungus B. salamandrivorans has been detected in Barcelona.…”
Section: Discussionmentioning
confidence: 99%
“…Cuban treefrogs can be infected with Bsal and, surprisingly, chytridiomycosis can develop in animals at the two highest zoospore dose exposures [ 126 ]. Moreover, different strains of Bsal might account for variations in susceptible species and epidemic profile, as was hypothesized following the isolation of Bsal in wild small-webbed fire-bellied toads ( Bombina microdeladigitora ) from Vietnam [ 121 , 127 ]. Current bans on amphibian transport that largely focus on halting the trade of urodele species may, therefore, be insufficient to prevent translocation of Bsal , especially as anurans constitute 99% of global amphibian trade [ 128 ].…”
Section: Overview Of Fungal Pathogensmentioning
confidence: 99%
“…In urodeles, only the terrestrial life stages are thought to be susceptible. Direct contact for at least eight hours is sufficient for transmission [ 118 ], although the delay between exposure and mortality in susceptible species is highly variable, ranging from 12–18 days in fire salamanders to seven weeks in gold-striped salamanders ( Chioglossa lusitanica ) [ 63 , 118 , 127 ]. In contrast to Bd , dermatological lesions present as multifocal ulcerative superficial epidermal lesions that are distributed over the entire body [ 63 , 64 ].…”
Section: Overview Of Fungal Pathogensmentioning
confidence: 99%
“…Like its sister species Bd, the pathogen was probably introduced through the international amphibian trade from its centre of origin in East Asia [13]. Being particularly lethal to salamander species, however, Bsal was projected to have devastating effects on salamander biodiversity hotspots, most notably in North and Central America as well as southern Europe [14][15][16]. Its emergence was therefore signalled as a key conservation threat that has the potential to strongly amplify the amphibian extinction crisis [17].…”
Section: Introductionmentioning
confidence: 99%